Amplification of the poorer ear by StereoBiCROS in case of asymmetric sensorineural hearing loss: effect on tinnitus - Potier, Morgan; Gallego, Stéphane; Fournier, Philippe; Marx, Mathieu; Noreña, Arnaud (Frontiers in Neuroscience, 2023)
Tinnitus is prevalent among patients suffering from Single-Sided Deafness (SSD) and Asymmetrical Hearing Loss (AHL). In addition to bothersome tinnitus in the poorer ear, these patients also report issues with understanding speech in noise and sound localization. The conventional treatment options offered to these patients to improve auditory abilities are cochlear implantation, bone conduction devices or Contralateral Routing Of Signal (CROS) hearing aids. It was recently found that the benefit of cochlear implantation for tinnitus associated with AHL/SSD was greater than the other two approaches. It is conceivable that the lack of stimulation provided to the poorer ear in these last approaches explains their modest impact on tinnitus perception. A new technology that combines the ability to reroute the sound from the poorer ear to the good ear (CROS system) while still stimulating the poorer ear with conventional sound amplification has recently been developed: the StereoBiCROS system. The aim of this study was to investigate the effects of this new device on tinnitus. Twelve AHL and two SSD patients aged 70.7 ± 7.9 years with tinnitus were fitted with bilateral hearing aids that included 3 programs: Stereophonic, BiCROS and StereoBiCROS (CROS + bilateral amplification). The short-and long-term effect of the approach on tinnitus was assessed using a tinnitus Loudness Visual Analog Scale (VAS) and the Tinnitus Handicap Inventory (THI), respectively. Both the VAS and the THI were used before and one month after the hearing aid fitting. Of the 14 patients who used their hearing aids daily (12.6 ± 1.6 h per day) the StereoBiCROS program was the most used program (81.8 ± 20.5% of the time). The average THI total score decreased from 47 (± 22) to 15 (± 16) (p = 0.002) and the VAS-Loudness score decreased from 7 (± 1) to 2 (± 2) (p < 0.001) after the one-month trial period. In conclusion, StereoBiCROS stimulation strategy seems to offer an effective alternative to reduce tinnitus handicap and loudness for patients with AHL/SSD and tinnitus. This effect may be driven by sound amplification of the poorer ear.